RUANG MESANIN PADA BANGUNAN DOMESTIK UNTUK MENCAPAI KENYAMANAN TERMAL - Yohana Nursruwening (Teodolita ( Media Komunikasi Ilmiah di Bidang Teknik ), 2009)
AbstractÂ Home is a place or environment created by humans for shelter and protection from enemy attack or other animals, as well as physical environment, cultural aspects, aspects of behavior and all aspects of human life. Home is the incorporation of several rooms where each room has a different activity. Because of differences in the activities that will be needed differentiator or room divider.The existence of a room in the house must be accompanied with the convenience for the purpose made space can be achieved optimally.Comfort room inside the house hanging from the ventilation system (air circulation). To solve the problem of the influence of climate in the tropics, then the application of space mesanin / split level on domestic building into a solution for comfort for the occupants to reach a successful buffer.Â Keywords: Space, mezanin, housing, thermal comfort, tropical architecture